2017
DOI: 10.48550/arxiv.1704.04854
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Copper Doping of BaNi$_{2}$As$_{2}$: Giant Phonon Softening and Superconductivity Enhancement

Kazutaka Kudo,
Masaya Takasuga,
Minoru Nohara

Abstract: The effects of copper doping on the structural and superconducting phase transitions of Ba(Ni1−xCux)2As2 were studied by examining the resistivity, magnetic susceptibility, and specific heat. We found an abrupt increase in the superconducting transition temperature Tc from 0.6 K in the triclinic phase with less copper (x ≤ 0.16) to 2.5-3.2 K in the tetragonal phase with more copper (x > 0.16). The specific-heat data suggested that doping-induced phonon softening was responsible for the enhanced superconductivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…Consistent with prior studies [28][29][30], the Ba 1−x Sr x Ni 2 As 2 system exhibits a discontinuity in the Debye temperature Θ D at x c . However, Θ D remains approximately constant between x = 0.71 (Θ D =198 K) and x = 0.86 (Θ D =188 K), despite a nearly two-fold difference in the superconducting T c .…”
Section: Isupporting
confidence: 86%
“…Consistent with prior studies [28][29][30], the Ba 1−x Sr x Ni 2 As 2 system exhibits a discontinuity in the Debye temperature Θ D at x c . However, Θ D remains approximately constant between x = 0.71 (Θ D =198 K) and x = 0.86 (Θ D =188 K), despite a nearly two-fold difference in the superconducting T c .…”
Section: Isupporting
confidence: 86%
“…The modeled heat capacity jump ∆C e /γT is ∼2.2, well above the BCS limit of 1.43, indicating strongly coupled superconductivity at this Co concentration. This value is consistent with previous reports of enhanced normalized heat capacity jumps of approximately 1.9 in both Ba(Ni 1−x Cu x ) 2 As 2 and BaNi 2 (As 1−x P x ) 2 [21,22] and greatly exceeds the near-BCS value observed in pure BaNi 2 As 2 [16]. While previous work on Cu-and Psubstituted BaNi 2 As 2 suggested that the enhancement in the tetragonal phase was consistent with a phonon softening picture, this is not the case here, as the enhancement occurs in the triclinic phase and the Debye frequency exhibits little change through the entire Co substitution range as noted above.…”
Section: Resultssupporting
confidence: 93%
“…Electronic structure calculations suggest BaNi 2 As 2 should not host an s ± state, as any nodal planes would necessarily intersect the Fermi Surface due to its complexity [20], and the heat capacity and thermal conductivity data of BaNi 2 As 2 has been well fit to a BCS s-wave model [16]. Despite the distinctions from its iron-based counterpart, previous substitutional studies in Ba(Ni 1−x Cu x ) 2 As 2 [21] and BaNi 2 (As 1−x P x ) 2 [22] have found an abrupt, strong enhancement of T c from 0.7 K to 3.3 K upon suppression of the triclinic phase [21,22], with strengthened pairing attributed to a soft phonon mode at the first-order structural phase boundary. The enhanced T c value in the tetragonal phase of BaNi 2 (As 1−x P x ) 2 extends to the x = 1 end-member BaNi 2 P 2 [23], suggesting the enhancement is rooted in the tetragonal structure itself.…”
Section: Introductionmentioning
confidence: 95%
“…Energetically low-lying phonons often result in strongcoupling superconductivity with an enhanced superconducting transition temperature T c . [1][2][3][4][5][6][7][8][9][10] Thus, engineering materials to produce low-lying phonons has become an important issue in superconductivity. A promising route to producing low-lying phonons is a local anharmonic vibration of the ion that is weakly bound in a cage-like structure.…”
mentioning
confidence: 99%
“…A remarkable example is the βpyrochlore oxide KOs 2 O 6 with T c = 9.6 K, [1][2][3][4] as well as Ba 3 Ir 4 Ge 16 with T c ≃ 6 K. 5,6) Another route to producing low-lying phonons is structural instability that becomes evident from the occurrence of a structural phase transition due to applied pressure or chemical doping. Prominent examples of such superconductors include the 122-type pnictides BaNi 2 (As 1−x P x ) 2 with T c = 3.3 K, 7) BaNi 2 (Ge 1−x P x ) 2 with T c = 2.9 K, 8) and Ba(Ni 1−x Cu x ) 2 As 2 with T c = 3.2 K, 9) all of which exhibit strong-coupling superconductivity because of a structural phase transition and the subsequent phonon softening characterized by an anomalously low Debye frequency. The MnP-type compound IrGe with T c = 4.7 K is a rare example that exhibits strong-coupling superconductivity with lowlying phonons but does not exhibit a structural phase transition.…”
mentioning
confidence: 99%